Women’s involvement in intra‐household decision‐making and infant and young child feeding practices in central Asia, No. 2 - Abdurazzakova, Dilnovoz; Kosec, Katrina; Parpiev, Ziyodullo (International Food Policy Research Institute, 2022)
2022 UPDATE: This paper examines the relationship between women’s empowerment and infant and young child feeding practices in Central Asia using Demographic and Health Survey data from 1995–2017. We employ a measure of women’s empowerment with three distinct dimensions available for a subset of recent surveys as well as a measure of a woman’s decision-making power over use of her own income present in all surveys. We identify a positive association between a woman’s decision making power—a measure of her instrumental agency—and adherence to World Health Organization–recommended feeding practices related to achieving minimum dietary diversity and minimum acceptable diet. We find little significant association between a woman’s attitude toward domestic violence, or her degree of social independence, and adherence to recommended feeding practices. Our results further show that women’s decision-making power has the greatest predictive power for adherence to optimal feeding practices among mothers living with a mother-in-law. In contrast, child gender and household poverty do not emerge as important moderators of the relationship between women’s empowerment and feeding practices. We thus provide evidence from Central Asia, a substantially under-studied region, that policies and programs expanding women’s decision-making power can improve child nutrition—especially when directed at extended households in which mothers cohabitate with in-laws. They suggest that all children would benefit—regardless of child gender and availability of complementary household resources.